1982
DOI: 10.1063/1.330910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on magnetic properties and morphology of iron particles

Abstract: Acicular iron particles with high coercivity and high saturation magnetization were prepared by reduction of the hematite particles which were obtained by dehydration of the silica-coated goethite particles in the process of heat treatment in air. Variations in specific surface area, micropore distribution, crystallite size, and magnetic properties with the dehydration temperature were measured. For the iron particles prepared by reduction of the silica-coated hematite particles obtained by dehydration at 800 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Thus, the Al/Fe + Co + Al mole ratio increased from 8% for the G CoAl sample to 33% for sample Fe CoAl (figure 5), indicating a further and more important enrichment of Al cations in the particle outer layers during its reduction process, which explains its role in avoiding interparticle sintering. In addition, it was observed that the proportion of cobalt in the particle outer layers decreased from goethite to iron for both Fe Co and Fe CoAl samples, respectively (figure 5), which suggested the diffusion of this cation to the inner part of the iron particles and, thereby, the formation of Fe-Co alloy, as previously observed by other authors [14,15]. Finally, the position observed for the Fe 2p 3/2 (710.3 eV) and Co 2p 3/2 (780.3 eV) XPS peaks (data not shown) was consistent with the presence of oxidized iron and cobalt in the particle outer layers, which could consist of a ferrimagnetic spinel phase similar to that suggested for Al-doped iron from Mössbauer studies [18].…”
Section: Preparation Of Iron Metal Particlessupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, the Al/Fe + Co + Al mole ratio increased from 8% for the G CoAl sample to 33% for sample Fe CoAl (figure 5), indicating a further and more important enrichment of Al cations in the particle outer layers during its reduction process, which explains its role in avoiding interparticle sintering. In addition, it was observed that the proportion of cobalt in the particle outer layers decreased from goethite to iron for both Fe Co and Fe CoAl samples, respectively (figure 5), which suggested the diffusion of this cation to the inner part of the iron particles and, thereby, the formation of Fe-Co alloy, as previously observed by other authors [14,15]. Finally, the position observed for the Fe 2p 3/2 (710.3 eV) and Co 2p 3/2 (780.3 eV) XPS peaks (data not shown) was consistent with the presence of oxidized iron and cobalt in the particle outer layers, which could consist of a ferrimagnetic spinel phase similar to that suggested for Al-doped iron from Mössbauer studies [18].…”
Section: Preparation Of Iron Metal Particlessupporting
confidence: 79%
“…Several studies have been carried out on the synthesis of Fe-Co MP from Co(II) adsorbed onto acicular goethite precursors [12,14,15]. However, this process involves the use of high temperatures (∼700 • C) to diffuse the Co toward the inner part of iron particles, leading to sintering between particles and the particles losing their acicular shape.…”
Section: Introductionmentioning
confidence: 99%
“…Giessen et al 1) reported that magnetic properties can be improved since in the case of absorbing Co 2þ and Ag þ on the oxide surface, the reduction rate at a low temperature becomes large, and in the case of absorbing Sn 2þ on the oxide particle, the reduction rate drops. Sueyoshi et al [2][3][4][5] reported that the iron particles prepared by reduction of silica-coated hematite particles showed excellent acicular shape and magnetic properties because of a diminished sintering of the iron particles. Ishikawa et al 6) also reported that the similar experimental results were obtained in the reduction of silica and cobalt coated hematite particles.…”
Section: Introductionmentioning
confidence: 99%
“…The acicular geothi te was dehydrated ln air, and reduced in hydrogen gas to iron acicular particles (7) • The reduction temperature was 450°C for sample A and 500°C for sample B. Figure 3 shows an example of TEM micrograph of sample A.…”
Section: Resultsmentioning
confidence: 99%